Experimental study of the ignition of lean methane/air mixtures using inductive and NRPD ignition systems in the pre-chamber and turbulent jet ignition in the main chamber. (15th January 2022) - Vera-Tudela, W.; Merotto, L.; Balmelli, M.; Soltic, P.
Highlights: Novel pre-chamber test rig with dual schlieren setups. Nanosecond repetitively pulsed discharge and inductive ignition systems. Spark ignition on the pre-chamber and turbulent jet ignition on the main chamber. Flame front propagation in pre-chamber affects ignition probability in main chamber. Ignition of very lean conditions is possible by combining NRPD and TJI. Abstract: The optimization of the combustion process in spark ignition engines has led to novel strategies to ignite lean and low reactivity mixtures, such as the application of turbulent jet ignition and Nanosecond Repetitively Pulsed Discharge (NRPD) ignition systems and Turbulent Jet Ignition (TJI). In the present experimental work, an optically accessible setup was used to investigate the ignition occurrence and early flame development in the pre-chamber and subsequent main chamber ignition of methane/air mixtures at density conditions relevant to engine application. Two schlieren setups coupled with fast recording cameras allow the visualization of both the pre-chamber and main chamber. NRPD ignition with different pulse patterns in terms of pulse number and repetition frequency is applied in the pre-chamber. Conventional inductive ignition and NRPD-assisted ignition are compared for the first time in terms of flame development in the pre-chamber and hot jet ignition in main chamber. The effect of different air to fuel ratios is assessed in both laminar and turbulent pre-chamber conditions. Results show that while NRPD is always advantageous when compared to standard inductive ignition, the higher amount of energy added by increasing the number of pulses only affects the ignition success in very lean conditions, thus showing that increased energy is not the main governing mechanism for successful ignition. Irrespectively of the initial conditions (laminar or turbulent) in the pre-chamber, it is shown that an optimum jet velocity exists that ensures increased ignition probability in the main chamber, thus suggesting that mixing plays a major role in main chamber ignition. The combination of both techniques, NRPD and TJI, allowed assessing the optimum conditions in terms of number and frequency of NRPD pulses for a reliable ignition in lean conditions.